Komunikasi Non Verbal Antar Lesbian: Studi Terhadap Mahasiswi Tertentu di Banda Aceh - Aininadhirah, Aininadhirah; Usman, A.Rani; Sulaeman, Arif Ramdan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study examines forms of nonverbal communication used by certain lesbian groups in Banda Aceh to build attraction and emotional comfort. Lesbianism is understood as an emotional relationship between women. The development of emotional closeness is influenced by nonverbal communication patterns that differ from typical same-sex interactions.The findings indicate that nonverbal communication in lesbian relationships is often expressed romantically through acts of service, facial expressions, gentle smiles, intense eye contact during interaction, and the use of compliments that foster comfort and emotional attraction. This study also highlights changes in attitudes and communication styles during conflict, reflected in differences in speech patterns and behavior. Feelings of jealousy also emerge when one partner develops closeness with another person . This study is significant as it relates to communication, social, and humanitarian aspects, particularly within societies strongly influenced by heteronormative norms. By understanding these nonverbal communication patterns, this research is expected to contribute to interpersonal communication studies and provide a more objective and humane perspective on the social realities of minority groups.